Religious Values in Bangilun Dance Verse and Its Pedagogical Relevance to Character Building - Pusparini, Noviana; Rohmadi, Muhammad; Wibowo, Prasetyo Adi Wisnu (Bina Nusantara University, 2021)
The research aimed to describe and identify the religious value contained in the poetry of Bangilun dance and its pedagogical relevance. Religious values were character values related to divinity: they were the basis of thought, speech, and deed. This value could be found in traditions such as the Bangilun dance as a manifestation of local wisdom. The research applied a the descriptive qualitative method. Data in the research were Bangilun dance poems that contained religious values. The data sources were informants, Bangilun dance poetry notebooks, journals, and books related to the selected topic. Data collection was done by using documentation, observation, and interview techniques. Data analysis technique used the content analysis method. The results show that form of religious values found in Bangilun poetry is a form of human relationship with God, while the pedagogical relevance is the Bangilun dance poetry can be used as teaching material in schools by including it in all school activities (extracurricular and intracurricular), integrating it in all subjects at all levels of education, and cooperation of all elements (school, parents, and society).